1999
DOI: 10.1037/h0089871
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between primary care physicians and mental health specialists.

Abstract: Primary care physicians (PCPs) are integral to the provision of mental health (MH) services. Linkages between PCPs and MHproviders are a vital component of care for psychiatric patients. This paper reports on an exploratory survey of PCPs about their relationships with mental health specialists. PCPs affiliated with Jefferson Medical College in Philadelphia, Pennsylvania were surveyed on the nature and quality of consultation and referral practices they had with individual mental health providers and mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…That is, physicians in solo and small‐group practices may have more difficulties obtaining referrals, because their patients' mental health services are managed by a separate entity with which the primary care physician has less experience. Other research has shown that primary care physicians perceive that mental health carve‐outs provide poorer quality of mental health care and report that they are less apt to share information about their patients with carve‐out providers 20 …”
Section: Discussionmentioning
confidence: 99%
“…That is, physicians in solo and small‐group practices may have more difficulties obtaining referrals, because their patients' mental health services are managed by a separate entity with which the primary care physician has less experience. Other research has shown that primary care physicians perceive that mental health carve‐outs provide poorer quality of mental health care and report that they are less apt to share information about their patients with carve‐out providers 20 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, collaborative communication practices remain inconsistent among practitioners and are frequently rated as unsatisfactory by both mental health and pediatric primary care providers. Numerous studies document pediatricians’ desire for increased feedback from mental health specialists (Pidano et al, 2011; Ross et al, 2011; Williams et al, 2005), yet also report that pediatricians communicate with mental health providers about referred patients less than half of the time (Ross et al, 2011; Yuen et al, 1999). Much less is known about mental health providers’ perspectives on collaborative communication with pediatricians.…”
mentioning
confidence: 99%
“…Research staff at the University of Connecticut Health Center developed and piloted the surveys for this project, based in part upon a survey developed by Pidano and colleagues (Pidano, Kimmelblatt, et al, 2011), with additions and revisions guided by published studies of mental health and primary care collaboration (Kainz, 2002; Williams et al, 2005; Yuen et al, 1999). The survey captured providers’ perceived satisfaction with current levels of communication and collaboration (rated on a 5-point scale ranging from “very dissatisfied” to “very satisfied”); perceived barriers to communication and collaboration (rated on a 4-point scale from “not at all a barrier” to “a large barrier”); and key markers of collaboration including: the frequency of referrals made or received between primary and mental health care providers in the past 6 months (“never,” “rarely,” occasionally,” or "frequently”), and the frequency and purpose (e.g., referral, follow-up care, case consultation) of phone or email contacts made or received between mental health and primary care providers in the past 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…Insufficient communication interferes with the continuity and coordination of care, and ultimately compromises treatment outcomes (Williams et al, 2005). While communication is a challenge amongst all primary care and specialty providers (Stille, McLaughlin, Primack, Mazor, & Wasserman, 2006), the gaps in the information that flows between primary care and mental health practitioners appear to be especially problematic (Foy & Perrin, 2010; Williams et al, 2005; Yuen, Gerdes, & Waldfogel, 1999). Surveys of pediatricians consistently reveal that they do not receive sufficient information from mental health clinicians to whom they have referred their patients (Gerdes, Yuen, Wood, & Frey, 2001; Ross, Chan, Harris, Goldman, & Rappaport, 2011; Williams et al, 2005).…”
Section: Improving Collaborative Practicementioning
confidence: 99%
See 1 more Smart Citation